A thorium metallacyclopentadiene complex: a combined experimental and computational study1. Issue 17 (7th May 2015) - Fang, Bo; Hou, Guohua; Zi, Guofu; Fang, De-Cai; Walter, Marc D.
<x xml:space="preserve">Abstract</x> The first thorium metallacyclopentadiene complex was prepared and its reactivity was investigated.